Low recurrence rate of hepatocellular carcinoma following ledipasvir and sofosbuvir treatment in a real-world chronic hepatitis C patients cohort - GÜNDÜZ, FEYZA (WILEY, 2019)
The aims of the present study were to evaluate the efficacy and tolerability of ledipasvir/sofosbuvir (LDV/SOF) with or without ribavirin in the treatment of chronic hepatitis C (CHC) in patients with advanced liver disease and to analyse whether the use of LDV/SOF treatment is associated with a new occurrence of hepatocellular carcinoma (HCC) during and after LDV/SOF treatment. The Turkish Early Access Program provided LDV/SOF treatment to a total of 200 eligible CHC patients with advanced liver disease. The median follow-up period was 22months. All patients were Caucasian, 84% were infected with genotype 1b, and 24% had a liver transplantation before treatment. The sustained virological response (SVR12) was 86.0% with ITT analysis. SVR12 was similar among patients with Child-Pugh classes A, B and C disease and transplant recipients. From baseline to SVR12, serum ALT level and MELD score were significantly improved (P<0.001). LDV/SOF treatment was generally well tolerated. Only one patient developed a new diagnosed HCC. Seventeen of the 35 patients, who had a history of previous HCC, developed HCC recurrence during the LDV/SOF treatment or by a median follow-up of 6months after treatment. HCC recurrence was less commonly observed in patients who received curative treatment for HCC compared with those patients who received noncurative treatment (P=0.007). In conclusion, LDV/SOF with or without ribavirin is an effective and tolerable treatment in CHC patients with advanced liver disease. Eradication is associated with improvements in liver function and a reduced risk of developing a new occurrence of HCC. Ledipasvir and sofosbuvir with or without ribavirin is an effective and tolerable treatment in hepatitis C virus-infected patients with advanced liver disease. Eradication is associated with improvements in liver function and reduces the risk of developing a new occurrence of hepatocellular carcinoma.
Keywords: cirrhosis; direct-acting antivirals; hepatitis C virus; hepatocellular carcinoma; liver transplantation; SUSTAINED VIROLOGICAL RESPONSE; UNEXPECTED HIGH-INCIDENCE; ACTING ANTIVIRAL THERAPY; ALL-CAUSE MORTALITY; VIRUS-INFECTION; PLUS RIBAVIRIN; RISK-FACTORS; GENOTYPE 1; LIVER; HCV